A Study on Controllable Mod Exploiting the Intrinsic Symmetry Breaking of Low-symmetry Photonic Crystals - Özgür Önder Karakılınç (MANAS: Journal of Engineering)
Photonic crystals are periodic dielectric structures that create photonic band gaps depending on the geometry of the lattice elements and the material properties. These structures allow light to be easily controlled, guided, and confined due to the tunability and adjustability of their design parameters. Conventional photonic crystals are typically designed with high-symmetry unit cells, while low-symmetry structures are created by breaking this symmetry. Low-symmetry structures are more sensitive to light manipulation and offer greater control and flexibility over light through geometric diversity. This study investigates the resonance effect in a cavity structure composed of a square lattice photonic crystal made of low-symmetry C2-type dielectric rods. The dependence of the resonance mode on the low-symmetry parameters was investigated and it was shown that, in contrast to other studies, mode splitting or merging can be achieved and tuned by exploiting and perturbing the intrinsic symmetry properties of the low-symmetry photonic crystal structure. The band structure, transmission spectra, and resonance frequencies of the low rotational symmetry photonic crystal were obtained using Lumerical and MEEP software. The analysis of resonance splitting and optical properties by symmetry manipulation will contribute to the understanding of light collimation and trapping.